Making room for the rancher - Jeffries, Christy (Harlequin special edition, 2021)
Looking after journalist Tessa King should have been a simple assignment for Secret Service agent Grayson Wyatt. But a family tragedy, and a social media faux pas, forces the vice president's famous daughter to hide out at her family's Wyoming ranch--and forces Grayson to play cowboy to blend in. Their attraction breaks every protocol--and threatens to expose Tessa's deepest secret. Worse, the media's chasing a story that could put everything the couple is fighting for at risk.